Uso de productos cotidianos en las prácticas de laboratorio de química orgánica: una estrategia metodológica basada en la investigación dirigida - Gutiérrez-Mosquera, Alexander; Barajas-Perea, Dary-Stella (Revista Científica, 2022)
The objective of this research is to design and implement a methodological strategy based on directed research to develop laboratory practices by using daily products within the organic chemistry course of the Academic Graduate Program in Natural Sciences (PALCN) from Universidad Tecnológica del Chocó. To fulfill this objective, we began with a diagnosis of the laboratory activities in said subject. This study was founded upon a mixed approach by means of a case study design. Theoretical, empirical, and statistical methods were used. The results obtained showed that, during the 2019-2 academic period, he teachers that make up the study sample did not conduct any laboratory practices and, when they guided laboratory activities, these were experiences, illustrative experiments, and practical exercises. As for the methodological strategy, the student and the group of experts expressed that the construction of school knowledge is favored from research by the contextualization of science, whose dynamic process makes it easier for them to understand and apply concepts, as well as to develop skills and positive attitudes towards chemistry from a research problem. Based on directed research, this methodological strategy allowed rethinking organic chemistry laboratory practices, encouraging an active role in the students and turning them into main actors within their education process.